Simultaneous Estimation of Pantoprazole Sodium and Levosulpiride in Capsule Dosage Form by Simultaneous Equation Spectrophotometric Method. (9th May 2013) - Shah, Dimal A.; Patel, Akash; Baldania, Sunil L.; Chhalotiya, Usmangani K.; Bhatt, Kashyap K.
Abstract : A simple, accurate, and precise spectrophotometric method was developed for simultaneous estimation of pantoprazole sodium and levosulpiride in capsule dosage form. Simultaneous equation was developed at 290 and 232 nm. The method was found to be linear in the range of 4–12  μ g/mL for pantoprazole sodium and 8–20  μ g/mL for levosulpiride while accuracy of the method was confirmed by recovery studies of capsule dosage form and was found to be 100.23–100.99% and 100.51–100.94% for pantoprazole sodium and levosulpiride, respectively, in their capsule dosage form. The proposed method was validated and found to be accurate and precise. The method was successfully applied for the estimation of pantoprazole sodium and levosulpiride from their capsule dosage form.